Individual and Group Behavior in Islamic Educational Institutions - Aisatun Nadroh; Junaidi Junaidi (Journal of Indonesian Progressive Education, 2026)
Human resource management (HRM) holds significant importance in shaping the quality and efficiency of educational institutions within the Islamic framework. This research aims to examine how HRM is applied and its influence on the satisfaction levels of various stakeholders in Islamic education. The focus is on crucial elements of HRM such as planning, hiring, training, and assessing performance, along with the obstacles faced during implementation. A qualitative descriptive method was used to gain a thorough insight into HRM practices from the viewpoints of teachers, administrative personnel, and organizational leaders. Data were gathered through observations, interviews, and documentation, then analyzed using techniques for data reduction, presentation, and conclusions. The results show that while HRM practices tend to be effective, particularly in planning and development which positively impacts institutional performance there are still improvements to be made in recruitment and performance evaluation due to a lack of structured and competency-focused methods. The findings also indicate a strong link between effective HRM and stakeholder satisfaction; institutions that excel in HRM practices generally report higher levels of trust and quality of services. Moreover, this research emphasizes the necessity of merging managerial skills with Islamic principles like trust and ethical responsibility. This combination fosters a more comprehensive HRM framework that sets Islamic education apart from traditional approaches. The findings imply that ongoing assessments, strategic hiring, and thorough development programs are crucial for enhancing HRM effectiveness. This study aids in creating a value-driven HRM model that promotes both professional excellence and ethical integrity in Islamic educational institutions.